Decolonizing Gendered Readings: Post-Colonial Indonesian Qur’anic Exegesis and the Reframing of Women in Islamic Discourse - Mala, Fiki Khoirul; Dany Buyung Yudha Prasetya; Muhamad Irfan Maulana; Faris Maulana Akbar (Journal of Ushuluddin and Islamic Thought, 2025)
This article examines how post-colonial Indonesian Qur’anic exegesis contributed to the reconstruction of women’s roles during the nation’s epistemic transition from colonial domination to decolonial self-definition. Drawing on Norman Fairclough’s Critical Discourse Analysis and hegemonic masculinity theory, the study analyzes Hamka’s Tafsīr al-Azhar and Hasbi Ash-Shiddieqy’s Tafsīr an-Nūr as two pivotal interpretive trajectories that shaped mid-20th-century Islamic thought in Indonesia. The findings reveal complementary discursive strategies: Hamka advances a moral-spiritual discourse that situates male-female relations within a balanced social fiṭrah and employs tafsir as a medium for national moral reconstruction, while Hasbi articulates a rational-reformist approach emphasizing justice, mutuality, and the historical functionality of gender roles. Both exegetes resist colonial and classical patriarchal hierarchies by reframing women not as passive subjects but as moral and civic agents in nation-building. The study’s primary contribution lies in demonstrating that post-colonial Indonesian tafsīr constitutes a distinct decolonial hermeneutic that recongures gender through three analytical dimensions: women’s morality, rationalization of roles, and epistemic repositioning within Islamic discourse.